INOCULAÇÃO DE AZOSPIRILLUM BRASILENSE ASSOCIADA A NÍVEIS CRESCENTES DE ADUBAÇÃO NITROGENADA E O USO DE BIOESTIMULANTE VEGETAL NA CULTURA DO MILHO - Müller, Tânia Maria (2013)
Three experiments were carried out in Guarapuava, Paraná, Brazil in 2011 with objective of evaluating the effect of inoculation with Azospirillum brasilense and different doses of nitrogen fertilization and use of biostimulant in corn crop. The experimental design was complete randomized blocks. The first experiment had six treatments (A. brasilense x biostimulant) with twenty replications; the second experiment had fifteen treatments (A. brasilense x nitrogen fertilization) with eight replications; and, the third experiment had ten treatments (biostimulant x nitrogen fertilization) with twelve replications. The treatments with inoculation were performed in seed treatment, seeding furrow and control (no inoculation). Five doses of nitrogen (N) were evaluated (0, 75, 150, 225 and 300 kg ha?¹ of N ha?¹) and the presence or absence of biostimulant application at V4 growth stage. Chlorophyll content, leaf area index, senescent leaves at flowering, total number of leaves, foliar nitrogen content, plant height, leaf insertion height, plant population, leaf index, yield, thousand grain mass, damaged kernels, number of rows per leaf, number of kernels per row and number of kernels per leaf were the characteristics evaluated. The inoculation of A. brasilense in seed treatment and seeding furrow provided increase in the agronomic characteristics evaluated. However, the biostimulant limited the crop yield. There was quadratic response in corn yield with increase of nitrogen doses and the maximum yield was obtained with 210 kg ha?¹ of N. Therefore, it was concluded that nitrogen doses and inoculation of A. brasilense provided increase in yield. Since the biostimulant application at V4 growing stage jeopardized the corn yield in this study, it would not be a recommended technology; nevertheless, it is recommendable to perform more experiments on this technology.